2019
DOI: 10.1016/j.celrep.2019.08.056
|View full text |Cite
|
Sign up to set email alerts
|

Affinity Maturation Enhances Antibody Specificity but Compromises Conformational Stability

Abstract: Graphical Abstract Highlights d Description of the biophysical properties of 400 human B cellderived antibodies d Human B cell-derived antibodies generally show ''drug-like'' developability profiles d Affinity maturation leads to reduced antibody polyreactivity and hydrophobicity d Somatic hypermutation is associated with decreased conformational stability SUMMARY Monoclonal antibodies (mAbs) have recently emerged as one of the most promising classes of biotherapeutics. A potential advantage of B cell-derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
99
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(120 citation statements)
references
References 50 publications
4
99
0
Order By: Relevance
“…Various studies have discussed the effect of affinity maturation on structural and dynamic properties ( James and Tawfik, 2003 ; Cauerhff et al, 2004 ; Schmidt et al, 2013 ; Adhikary et al, 2015 ; Jeliazkov et al, 2018 ; Shehata et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Various studies have discussed the effect of affinity maturation on structural and dynamic properties ( James and Tawfik, 2003 ; Cauerhff et al, 2004 ; Schmidt et al, 2013 ; Adhikary et al, 2015 ; Jeliazkov et al, 2018 ; Shehata et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Besides developability traits that are constantly present in Abs, some unfavourable characteristics can be cryptic and thus become apparent only after exposure of Ab molecule to certain conditions. Thus, in addition to intrinsically polyreactive Abs that express their antigen-binding promiscuity constantly (18,19), a fraction of human Abs can acquire potent polyreactive behaviour posttranslationally upon in vitro or in vivo exposure to redox-active substances, including the physiologically-relevant cofactor heme (20)(21)(22)(23)(24). Notably, by analyses of a set of 9 therapeutic Abs approved for treatment of cancer, it was demonstrated that after exposure to heme most of the Abs acquired substantial polyreactivity (25).…”
Section: Introductionmentioning
confidence: 99%
“…Elucidating the affinity maturation process has been the focus of numerous studies (Cauerhff et al, 2004;Cho et al, 2005;Acierno et al, 2007;Li et al, 2010;Wong et al, 2011;Adhikary et al, 2015;Jeliazkov et al, 2018;Mishra and Mariuzza, 2018;Fernández-Quintero et al, 2019b;Shehata et al, 2019;Chan et al, 2020). Upon affinity maturation (Figure 5), we observe for the matured F10.6.6 antibody in both V H -V L interface and elbow angle histograms ( Figure 5B) a narrower distribution, compared to the broader surface of the D44.1 Fab ( Supplementary Table S1).…”
Section: Discussionmentioning
confidence: 75%